Electrochemical additive manufacturing of NiCoFeCuMo high entropy alloys using a combined dissolution-deposition system. Issue 1 (2022) - Sundaram, M.; Brant, A.; Rajurkar, K.
Abstract: Compositionally-graded NiCoFeCuMo high-entropy-alloy parts were fabricated using electrochemical additive manufacturing operated in a combined dissolution-deposition manner. Dynamic solution concentration control and compositional grading were achieved using concurrent dissolution of source metal anodes. A common supporting bath to accommodate dissolution and deposition of all metals was identified by separately studying dissolution processes and selecting ionic influences on deposition. Results from the combined system showed that Ni and Mo contents could be graded the most controllably, followed by Co and Fe, and finally Cu. Output atomic percentages ranged from 3-48%, with some regions meeting the 5-35% definition of a high entropy alloy.